Aprendizagem e desenvolvimento da linguagem oral no contexto da educação infantil - Costa, Wanessa Rafaela do Nascimento da (2014)
In the course of development of each individual, the language has, from the perspective of approach cultural-historical of L.S. Vygotsky, an important role of mediation in the constitution psychological, whose form of operation has originated in social life, in the interactions with the culture and which it develop through of internalization of inter-mental modes of action, that become intra-mental modes. In this perspective, the parlance itself, as a function specifically human , develops in each child upon its insertion in the sociocultural environment, since the first months of life, evolving significantly in the first and second year, not naturally, but in situations of interaction and mediation of others people with whom they live. Our study has been originated of these presuppositions together with the recognition of the social role of childhood education to promote the holistic development of children, which includes the learning of symbolic practices or multiple parlances, among them the oral language practice. We ask ourselves about: in what situations experienced by children of one to two years, in the context of a nursery, the learning and the development of oral language are favored and what is the role of the teacher and of children? This work aims to analyze contexts / situations of appropriation of oral language in infants and children in childhood education and the role of the other(s) - teachers and other children - in that process. The study assumed, theoretically and methodologically, the principles of approach cultural-historical of LS Vygotsky and the dialogism of M. Bakhtin on the development of human processes and its analysis. It has been developed into a Municipal Center of Childhood Education of Natal / RN and involved the construction of empirical data through of participatory observations of daily dynamic, with video recording and field diary. The subjects were six teachers who work with a group of fifteen children in a class of second level of nursery. The data analysis allowed us to coalesce into two groups experienced situations in which the nursery show signs emergency oral language - role of children and teachers: 1) this is triggered by the children themselves: events among children themselves and events among children and teachers; 2) violations caused by Professors: members of routine events (wheel of time and moment of watching TV-DVD) and events outside of the routine moments. While we recognize the importance of interaction between children and their undeniable ability to participate and produce events as learning possibilities, we highlight the role of teachers in those moments, because they are the responsible adults who can see, hear and give meaning to all actions of the children, as well as organize and propitiate, in their practices, situations in which the children can live experiences of / with the a richest language and which provides its development. Finally, we highlight the need for the oral language - its nature and learning - go on to have a more prominent place in the organization of tenders and pedagogical practices of education for children in childhood education and therefore in the formation of teachers working at this stage.